Air pressure effect on growth behaviour of two different Kluyveromyces strains - Pinheiro, Rita (1998)
In the past decade, yeasts other than Saccharomyces cerevisiae have gained industrial interest. Examples are the lactose-utilising species Kluyveromyces lactis and K. marxianus. This type of yeasts are often proposed for reducing the BOD of cheese whey and other dairy plant wastes, for the production of flavours, enzymes and antibodies as well as for the expression of proteins. Their application in large-scale fermentations may be common industrial practice before the end of this century [1]. The use of pressure as a way of enhancing oxygen transfer rate to bioreactors can be investigated because oxygen is a major growth limiting factor in high density aerobic cultures. In biological processes the traditional way of improving oxygen transfer rate, by increasing stirring rate, has several limitations, like power consumption and cell damage, due to mechanical effects. The attempt to improve bioreactor performance has therefore been directed toward a reduction of the mechanical stress responsible for the cell inactivation [2]. The effect of increased air pressure on the biomass yield and ethanol yield of two Kluyveromyces strains was investigated. K. marxianus ATCC10022 is a lactosefermenting strain whereas K. marxianus CBS 7894 has a Kluyver-effect for lactose. For K. marxianus ATCC10022 the air pressure increase of 2 bar, led to a 3 fold increase in biomass yield. It was also possible to enhance ethanol oxidation of cell yeasts by increasing air pressure. Batch cultures of K. marxianus CBS 7894 exhibited a different growth behaviour as K. marxianus ATCC10022: its metabolism was always oxidative and ethanol was never produced. With the increase of air pressure it was possible to increase biomass yield as well as the specific growth rate. On the other hand, as far as oxidative stress is concerned, antioxidant enzymes, such as superoxide dismutase, catalase and glutathione reductase, were not at high activities levels suggesting that there were no toxic effects on yeast cells for the studied pressures.